Identification of single-stranded-DNA-binding proteins that interact with muscle gene elements. - Santoro, I M (1991)
A sequence-specific DNA-binding protein from skeletal-muscle extracts that binds to probes of three muscle gene DNA elements is identified. This protein, referred to as muscle factor 3, forms the predominant nucleoprotein complex with the MCAT gene sequence motif in an electrophoretic mobility shift assay. This protein also binds to the skeletal actin muscle regulatory element, which contains the conserved CArG motif, and to a creatine kinase enhancer probe, which contains the E-box motif, a MyoD-binding site. Muscle factor 3 has a potent sequence-specific, single-stranded-DNA-binding activity. The specificity of this interaction was demonstrated by sequence-specific competition and by mutations that diminished or eliminated detectable complex formation. MyoD, a myogenic determination factor that is distinct from muscle factor 3, also bound to single-stranded-DNA probes in a sequence-specific manner, but other transcription factors did not. Multiple copies of the MCAT motif activated the expression of a heterologous promoter, and a mutation that eliminated expression was correlated with diminished factor binding. Muscle factor 3 and MyoD may be members of a class of DNA-binding proteins that modulate gene expression by their abilities to recognize DNA with unusual secondary structure in addition to specific sequence.